Analisis Preservasi Preventif Perpustakaan Hukum Mochtar Kusumaatmadja Dalam Aspek Keamanan Koleksi Bahan Pustaka - Rahmi, Syahla Nurlaeli; Saleha Rodiah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
The library is an institution that manages various information resources. So it is necessary to take action in the form of carrying out the preservation process properly and correctly, both preventively and curatively. This is because the collections in the library can be damaged and destroyed at any time either due to environmental or human factors so that appropriate preservation or preservation measures are needed. This study uses qualitative research methods with data collection methods from literature studies and interviews. Using data collection techniques in the form of observation by visiting the Mochtar Kusumaatmadja Law Library, which is located on the university campus, Jl. Dipati Ukur No. 35, Lebakgede, Coblong District, Bandung City, West Java. The author also conducted interviews with one of the library staff who manages the collection of library materials. The purpose of this study was to determine the extent to which Mochtar Kusumaatmadja's legal library maintains library security, both the security of book collections and the security of the building. According to the author's observations, he found that the security system in the law library is bad and far from good, this is caused by many factors and what greatly affects this is the lack of budget and lack of human resources (HR) in the library. It is unfortunate that the library already has an adequate building but the library in it is not managed optimally, especially on the HR factor it is very visible that the division of work shifts looks unfair because only a staff who almost does all the work in the library starting from maintenance, management library materials, even to the point of taking over the circulation and reference services department. After doing this research, the author hopes that the Mochtar Kusumaatmadja law library can continue to improve its security system for the better so that both librarians and users can feel safe and comfortable while in the library environment.